BATU TETERUGA DAN CERITA RAKYAT SUKU SOBEY: Batu Teteruga and The Sobey Tribe Folktale - Rini Maryone (BALAI ARKEOLOGI PAPUA, 2021)
Megalithic dwellings in Papua related to folktale are very much traced from each region. These folktale are not only told by the community but there is historical evidence in the form of natural stone buildings. Which according to archaeology is called megalithic buildings. The stone is believed to be a deformed turtle. This research was conducted in Kampung Bagaiserwar Sarmi Kota district, Sarmi Regency, Papua Province. In this paper the author uses the method of ethnoarkeological approach. This research is also conducted in two stages, namely data collection and data processing. Data collection is done in several ways, namely: surveys, interviews and conducting library studies. The final stage is data processing, after all the collected data is then described, analyzed and interpreted. By using this method, you can also find out the megalithic remains of the suspect stone /turtle and folktale of the Sobey tribe in Sarmi Regency and can know what cultural values are contained in the megalithic dwellings and folktale of teteruga/ turtles / in the Sobey tribe in Sarmi Regency.